2022
DOI: 10.1111/1759-7714.14629
|View full text |Cite
|
Sign up to set email alerts
|

Radial‐EBUS and virtual bronchoscopy planner for peripheral lung cancer diagnosis: How it became the first‐line endoscopic procedure

Abstract: Background Various advanced bronchoscopy methods have been developed to reach peripheral lung lesions (PLL). In a large cohort, we aimed to assess a standardized procedure of first‐line radial‐endobronchial ultrasound (r‐EBUS) and virtual bronchoscopy planner for the diagnosis of peripheral lung cancer. Methods This retrospective, single center study included patients who had r‐EBUS‐guided bronchoscopy for the diagnosis of a PLL between 2008 and 2019. Cases without a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The diagnostic yield of rEBUS for PPL biopsy in our study was consistent with previously reported values, with an overall yield of 78.8% ( 7 , 8 ). In line with previous studies, the presence of a direct (type A) bronchus sign and a concentric rEBUS orientation were strong independent predictors of a successful rEBUS procedure ( 7 , 17 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The diagnostic yield of rEBUS for PPL biopsy in our study was consistent with previously reported values, with an overall yield of 78.8% ( 7 , 8 ). In line with previous studies, the presence of a direct (type A) bronchus sign and a concentric rEBUS orientation were strong independent predictors of a successful rEBUS procedure ( 7 , 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…Meta-analyses have revealed a diagnostic yield of approximately 70.6% for the rEBUS procedure, accompanied by a very low overall complication rate of only 2.8% ( 7 ). Over the years, rEBUS procedure has continued to evolve with the addition of more automation technology to enhance its performance, such as virtual bronchoscopic navigation (VBN) for pre-procedural planning, electromagnetic navigational bronchoscopy (ENB) for real-time tracking, and most recently, the use of robotic bronchoscopy systems ( 8 - 10 ). However, these advanced technologies are not readily available in all parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutation testing is becoming increasingly important for lung cancer management, and the usefulness of r-RBUS with guide sheath, conventional virtual bronchoscopic planners (e.g., LungPoint, etc. ), and electromagnetic navigation systems has been reported [8][9][10] . Our results indicate that ultraselective bronchoscopy using ultrathin bronchoscopy combined with precise bronchoscopic planner (DOM) and r-EBUS is also useful for obtaining the volume of small distal PPL samples sufficient for NGS-based tumor analysis, displaying a fairly successful instance of precision medicine by adjustment, from a pathological point of view.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, patients with peripheral lung nodules suspicious of lung cancer were routinely subjected to r-EBUS with the GS technique for diagnosis as described elsewhere. 5 , 6 …”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, in approximately 30% of cases, these samples are noncontributory for genomic analysis owing to a lack of available tumor tissue. 5 , 6 , 7 In this context, ctDNA analysis could represent an alternative for genomic characterization.…”
Section: Introductionmentioning
confidence: 99%